Performance Of Actual And Laboratory Horizontal Roughing Filter For Turbidity And E.COLI Removal - Zuraidi, Wan Muhammad Adib Wan (Universiti Sains Malaysia, 2017)
Roughing filtration is one of water treatment methods which has been used widely throughout the world. Roughing filtration has been used as major water treatment in rural water supply systems because of its advantages that can be maintained easily, does not need any chemicals, has long operational time and can be operated and maintained by trained local caretakers. Its effectiveness to remove turbidity, suspended solids, and coliform organism has been proved by various researchers whether at laboratory-scale or pilot-scale study. However, performance of actual roughing filter is still not well understood. Therefore, this present study was conducted to evaluate the performance of actual-scale roughing filter. In this study, the removal efficiency of actual-scale which is located at Kg. Sungai Air Simpul, Ijok, Selama, Perak and laboratory-scale horizontal roughing filter to remove water turbidity and E.coli concentration were tested and compared. The laboratory roughing filter also tested using 3 different flow rates in order to determine the effect of applied flow rate of roughing filter. In addition, adsorption study was conducted to investigate the adsorption capacity of limestone filter media for turbidity removal. The experimental results indicate that the performance of actual roughing filter for turbidity and E.coli concentration were in range with the results obtained from laboratory. This experimental result also shows that the removal efficiency of roughing filter increase as the applied flow rates decrease. Meanwhile, results from adsorption study revealed that Langmuir Isotherm fitted the experimental data better than Freundlich Isotherm for turbidity adsorption. In Langmuir Isotherm, the maximum adsorption capacity of Limestone for turbidity was 0.002 NTU/g.